PENYEDERHANAAN BIROKRASI DAN TRANSFORMASI KELEMBAGAAN DEMI MEWUJUDKAN PELAYANAN PUBLIK YANG PRIMA DI LINGKUNGAN PEMERINTAH PROVINSI JAWA BARAT - Harky Ristala; Muhammad Aldi Rahmandika (Jurnal Academia Praja, 2022)
Bureaucracy simplification and institutional transformation are the urgency of the current government. This is not only because of the mandate of the Central Government Regulations, but also the demands of the people who expect fast and accurate public services. The presence of excellent public services can be realized by the presence of agile organizations that take advantage of the conditions of collaboration between fields through their functional positions. The West Java Provincial Government responds to the mandate and demands of the community by realizing Bureaucracy Simplification and Institutional Transformation in order to create excellent and fast and accurate public services.